Isolated Rheumatic Mitral Regurgitation with Giant Left Atrium in Sinus Rhythm A Case Report - Kabir, Md Faisal Ibn; Amin, Md Rasul; Mandol, Mohammad Rayhan Masum; Joarder, Md Ariful Islam; Mahabub, Sm Ear E; Khaled, Md Fakhrul Islam; Haque, Mustashirul; Bajracharya, Prashant; Ahmed, Khurshed; Hoque, Md Harisul (University Heart Journal, 2017)
A 30-year-old woman, patient of severe MR with pulmonary hypertension presented with symptoms. On evaluation, giant left atrium was found on echocardiography (65 mm). Most strikingly, the patient was still in sinus rhythm. She was managed medically and after stabilization of symptoms, discharged with advice for mitral valve surgery and regular follow-up. University Heart Journal Vol. 12, No. 1, January 2016; 51-54